Mental health nursing: Daring to be different, special and leading recovery‐focused care?. (3rd February 2017) - Santangelo, Peter; Procter, Nicholas; Fassett, Denise
Abstract: How mental health nursing is differentiated from other disciplines and professions, and what special contribution mental health nurses make to health services, is a question at the heart of contemporary practice. One of the significant challenges for mental health nurses is identifying, developing and advancing those aspects of their practice that they consider differentiate them in the multi‐disciplinary mental health care team and to articulate clearly what a mental health nurse is and does. This paper draws on data from interviews with 36 mental health nurses in Australia who identified their practice as autonomous. Participants were asked the question, "What's special about mental health nursing?" Constructivist grounded theory techniques were applied to the research process. Findings were formulated and expressed as the 'Ten P's of the professional profile that is mental health nursing', which are 'present', 'personal', 'participant partnering', 'professional', 'phenomenological', 'pragmatic', 'power‐sharing', 'psycho‐therapeutic', 'proud' and 'profound'. The combined elements of the findings present a theoretical construct of mental health nursing practice as something distinctive and special. It provides a model and exemplar for contemporary practice in mental health nursing, embracing the role of mental health nurses in the health care workforce as being well placed as providers of productive and effective care.